Covid-19 e saneamento básico: relações e impactos - Silva, Rafaela Alves Vicente Rodrigues da (2022)
This work proposes to establish the theoretical-scientific aspects that allow to perceive the effects of basic sanitation in the prevention and combat of pandemics caused by viruses, mainly, the current pandemic of COVID-19. Making connections between concepts and things, based on a broad bibliographic investigation that allows extracting important information on the thematic axis contained in the coronavirus-basic sanitation binomial. The research developed is of an exploratory type combined with a descriptive one, with a quali-quantitative approach. Classic materials, government platforms and scientific publications were consulted. COVID-19 reinforced the importance of access to basic sanitation for public health. However, it is difficult to guarantee hygiene actions when not everyone has access to treated water, sewage collection and treatment. Some of the factors that may be associated with the incidence of cases or mortality rates of this disease are sanitation conditions. The main route of transmission of the virus is via contaminated aerosols and respiratory droplets. However, the presence of the genetic material of SARS-COV-2 in the feces of infected people aroused interest in studies related to the possibility of oral-fecal transmission through untreated sewage, contaminated water supply and even the bioaerosols produced in ETEs. Due to the high number of infected people, there is an interest in analyzing other possible routes of transmission and how access to sanitation in Brazil influences the fight against the disease, since the persistence of the virus in the environment has not yet been completely clarified. The Brazilian population is estimated at more than 200 million inhabitants distributed throughout the five macro-regions with different demographic densities, sociocultural aspects and access to sanitation services. The North and Northeast macro-regions have the worst rates of water supply, sewage collection and treatment. Despite this, these regions had lower rates of cases and deaths from COVID19. On the other hand, two of the best regions served by basic sanitation services, the Midwest and Southeast, had the highest accumulated deaths until June 2022. It can be seen that the lack of sanitation has been causing long-term deaths from waterborne diseases in the However, with investments in the sanitation sector, it is possible to reduce the number of hospitalizations and deaths, in addition to assisting in preventive measures to combat infectious diseases. It was also found that poor sanitation is not the only vector capable of influencing the spread of the disease. But it can be an aggravating factor, considering that 16% of the Brazilian population do not have access to the water supply network, and are those who adhere to dubious water sources, without confirmation that it is within the potability standard for human consumption, becoming more vulnerable to waterborne diseases. As for the monitoring of SARS-COV-2 in sewage, it can be a useful tool to monitor new outbreaks of COVID-19. So far, there is no scientific evidence that proves fecal-oral or fecal-respiratory transmission, however, it is pertinent to continue in-depth research on the persistence and viability of the virus in the environment, especially in aquatic matrices. As well as the fate of Sars-Cov-2 in treatment plants, analyzing the performance of virus removal in the stages.